Entertainment apps, limited attention and investment performance - Zhang, Yingxin; Du, Yijing; Li, Yan (Frontiers in Psychology, 2023)
After welcoming the "Information Age", investors are now encountering a "Mobile Age" associated with profound changes to daily life worldwide. In response, investors must process more information while experiencing increasing mobile phone-related distractions, particularly those generated by the fast-growing entertainment-type app industry. Attention is a limited cognitive resource vital for deliberate and thoughtful analysis. Using data from an online peer-to-peer lending market, we found that investors with a large number of mobile phone entertainment apps were more likely to show higher default rates and lower investment returns. The results are robust using exogenous natural internet service outage of the entertainment server and instrumental variables, suggesting that investors' attention is distracted by these mobile apps. Besides, the negative performance effect is more pronounced on Fridays and in high internet speed regions. The mechanism analysis showed that lower performance bidding behaviors were subject to information neglect and familiarity heuristics when distracted by more entertainment-type apps.